O ser da guerra e a guerra do ser: O Prisioneiro, de Erico Verissimo, como um dispositivo-lúdico-profanatório - Luckner, Rita de Cassia Scocca (2022)
The scope of this work is to present the transforming function of literature through theological-literary analysis of the O Prisioneiro, written by Erico Verissimo, (1967), by means of symbolic language, of the playing with the words, of said and no-said and of the message pointed by the literary verb make possible to highlight the elements relating to the human behavior who is captured in several levels to the power, represented by the characters and context portrayed in the novel. Onwards conceptions of dialogism, by Mikhail Bakhtin, dispositive and profanation, by Giorgio Agamben, the focus is to address about the fall of the language, which is monologic (sacralized) by excess, to then ascend and reveal itself dialogic (profane). Our assumption is that the conceptions about language developed by these theorists, studied and interconnected in this research, contrasted with the analysis of the novel, allow us to highlight the quality of dispositive-ludic-profanatory of the literature, particularly in O Prisioneiro, and emphasize its proficiency, of an anthropological nature and in constant dialogue with theology, both in representing and expanding meanings within the set of individual and collective of human beings, that leads us to apprehend the potentiality of human language and the revelation of the virtue of prudence and brings new meanings and interpretations of realities, becoming a way to renewal, growth and retaking the critical and active attitude of being. (AU)